CHALLENGES TO THE SCARCITY OF FARMWORKERS, IT’S INFLUENCE ON THE PRODUCTIVITY OF SUGARCANE CROP IN THE PHILIPPINES - Dr. Paulino A. Oñal, Jr.; Dr. Ma. Corazon G. Acaba; Anabelle P. Guarin (European Journal of Agricultural and Rural Education, 2022)
The present status of sugarcane farming in the Central Philippines has very low productivity, especially in areas with 10.0 hectares and below. Doloriel (2014) confirmed in her study that sugarcane farming is productive and profitable only for medium and large-sized farms. The findings further confirmed that small sugarcane areas are not profitable, which is 79.0% of 424,199 hectares, the total area planted for sugarcane for the whole Philippines. The descriptive method of research aid in determining the relationship between the number of farmworkers and the productivity of sugarcane farmers in the Central Philippines. The 400 sugarcane farmers were randomly identified at the different locations. An instrument used was the Agency Extension Program Guideline which measures the productivity and the level of management of the farmworkers. The result shows that the level of productivity of sugarcane farms in the Central Philippines was “high”. Using an ANOVA shows a significant difference in the level of productivity of sugarcane farms when grouped as to the location (F=3.482, p=.000<0.05). Furthermore, there is a significant difference (F-value 6.921, sig. at .000) between productivity and the number of farmworkers per hectare. Farmworkers were “moderately compensated” (M=2.59) and “moderately available” (M=2.56), too. Overall, there is a strong relationship between the number of farmworkers and the farmer’s productivity. It is recommended that more studies should be conducted related to this subject, to contribute to the pool of knowledge related to the importance of farmworkers with the productivity